Impact of nitrogen fertilizer timing on nitrate loss and crop production in northwest Iowa. Issue 4 (20th June 2022) - Waring, Emily Rose; Sawyer, John; Pederson, Carl; Helmers, Matt
Abstract: In the U.S. Midwest, nitrate in subsurface tile drainage from corn ( Zea mays L.)–soybean [ Glycine max (L.) Merr.] systems is detrimental to water quality at local and national scales. The objective of this replicated plot study in northwest Iowa, performed in 2015–2020, was to investigate the influence of nitrogen (N) fertilizer timing on crop production and NO3 load in subsurface (tile) drainage discharge. Four treatments applied to corn included fall anhydrous ammonia with a nitrification inhibitor (F), spring anhydrous ammonia (S), split‐banded urea at planting and mid‐vegetative growth (SS), and no N fertilizer (0N). Across crops and years, NO3 –N concentration in subsurface drainage discharge was the same at 11.7 mg L –1 for F and S applied anhydrous ammonia (AA). The NO3 –N concentration was statistically lower with SS urea (10 mg L –1 ) than F and S, and 0N was lower than SS at 8.3 mg L –1 . Average annual NO3 –N loads were not different between any treatments due to plot variability in drainage discharge. Corn responded to N application, with overall mean yield the same for F, S, and SS. There were no agronomic or water quality benefits for applying AA in spring compared with fall, where the F included a nitrification inhibitor and was applied to cold soils. Split‐applied urea had a small positive water quality impact but no crop yield enhancement. This study shows that there were improvements to NO3 –N concentration in subsurface drainage discharge, but more nutrient reduction practices are needed than fertilizer N management alone to reduce nitrate load to surface water systems. Core Ideas: Spring‐applied AA compared with fall anhydrous ammonia (AA) with nitrapyrin did not reduce NO3 –N concentration in drainage discharge. Split‐applied urea decreased NO3 –N concentration in drainage discharge compared with fall and spring AA. Spring and fall AA had the same corn yields, but split‐applied urea decreased corn yield in a dry year. Even with no N applied, there was considerable NO3 loading in both corn and soybean crops.